Unexpectedly large myoepithelioma-like tumor of the vulvar region with two local recurrences: A rare case report and review of the literature - Soheila Aminimoghaddam; Soheila Sarmadi; Mahdis Kashian; Niloufar Sarchami (Elsevier, 2023)
Myoepithelioma-like tumors of the vulvar region (MELTVR) are rare. Only a limited number of MELTVRs are reported in the literature, and various aspects of this lesion still need to be clarified. In this study, we reported a case of MELTVR in a 46-year-old female. The uniqueness of the present case was its large size (12 cm) compared to the MELTVRs reported in earlier studies, the presence of two separate but attached lesions (one in labia majora and one in the mons pubis), and two recurrences within ten years after wide local excision. The second recurrence was managed with wide excision, and the patient remained disease-free during the two-year follow-up. This case highlights the local aggressiveness of MELTVR and the necessity of resection with an adequate margin. It also urges more awareness regarding the differential diagnosis of MELTVR with other lesions of the vulva, particularly when located in the labia majora and mons pubis.